Core and Bargaining Set of Shortest Path Games - Sofia Grahn (Uppsala University, Department of Economics, 2001)
In this paper it is shown that the core and the bargaining sets of Davis-Maschler and Zhou coincide in a class of shortest path games.
Keywords: C70; 330; Shortest path games; core; bargaining set; Core; Spieltheorie; Theorie